2006
DOI: 10.1128/jvi.80.6.2873-2883.2006
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Human Immunodeficiency Virus Type 1 Replication with Artificial Transcription Factors Targeting the Highly Conserved Primer-Binding Site

Abstract: The human immunodeficiency virus type 1 (HIV-1) primer-binding site (PBS) is a highly conserved region in the HIV genome and represents an attractive target for the development of new anti-HIV therapies. In this study, we designed four artificial zinc finger transcription factors to bind at or adjacent to the PBS and repress transcription from the HIV-1 long terminal repeat (LTR). These proteins bound to the LTR in vivo, as demonstrated by the chromatin immunoprecipitation assay. In transient reporter assays, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 61 publications
2
47
0
Order By: Relevance
“…Synthetic zinc finger DNA-binding proteins have been generated for many sequences, using several approaches (15)(16)(17). Capitalizing on this work, researchers have incorporated synthetic zinc finger proteins into a wide variety of molecular tools (7,(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29).…”
mentioning
confidence: 99%
“…Synthetic zinc finger DNA-binding proteins have been generated for many sequences, using several approaches (15)(16)(17). Capitalizing on this work, researchers have incorporated synthetic zinc finger proteins into a wide variety of molecular tools (7,(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29).…”
mentioning
confidence: 99%
“…ZF-TFs have been previously used in strategies to control replication and/or infection by viruses, including the DNA virus herpes simplex virus and the retrovirus HIV (Eberhardy et al 2006;Kim et al 2005;Papworth et al 2003;Reynolds et al 2003;Segal et al 2004), in mammalian cells. Sera (2005) described a ZF-TF that restricts the replication of the single-stranded-DNA-containing Geminivirus beet curly top virus by binding to the origin of replication.…”
Section: Discussionmentioning
confidence: 99%
“…Early work on the use of engineered zinc-finger transcription factors revealed that synthetic transcriptional modulators are effective tools for a broad range of applications, enabling such tasks as inhibiting viral replication (Papworth et al 2003;Reynolds et al 2003;Segal et al 2004;Eberhardy et al 2006), modulating the expression of disease-associated loci (Graslund et al 2005;Wilber et al 2010), inducing angiogenesis for accelerated wound healing (Rebar et al 2002), and genomic screening of cellular targets for cancer progression and drug resistance Blancafort et al 2005Blancafort et al , 2008. Facilitated by many of the insights gained from zinc-finger transcription factor technology, both TALEs and CRISPR-Cas9 have now further expanded the possibilities of engineered transcriptional activators and repressors.…”
Section: Applications Of Targeted Transcriptional Regulationmentioning
confidence: 99%